2013
DOI: 10.1080/02602938.2013.803027
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of synergetic peer assessment: first-year experience

Abstract: Active participation in learning activities and reviewing assessment activity can facilitate learners engaged in these processes. This case study reports student experiences of the process of peer assessment with teacher guidance in a group project for a first-year nursing course with 153 students. Twenty groups of students were assigned roles in exploring one of the two scenarios: one involved analysing diabetes mellitus and the other considered colorectal carcinoma, in each case covering provision of acute n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
1
10
0
1
Order By: Relevance
“…Providing quality critique in peer review does not come naturally to students (Hodgson et al, 2014), so it is imperative to provide opportunities for discussion of criteria and standards and to teach students evaluative skills if peer review is to be effective (Hodgson et al, 2014;Yucel et al, 2014). Mostert and Snowball (2013), for example, found that students believed they had put effort into providing feedback but did not receive adequate feedback in return.…”
Section: Principle 4: Provide Opportunities To Act On Feedbackmentioning
confidence: 99%
“…Providing quality critique in peer review does not come naturally to students (Hodgson et al, 2014), so it is imperative to provide opportunities for discussion of criteria and standards and to teach students evaluative skills if peer review is to be effective (Hodgson et al, 2014;Yucel et al, 2014). Mostert and Snowball (2013), for example, found that students believed they had put effort into providing feedback but did not receive adequate feedback in return.…”
Section: Principle 4: Provide Opportunities To Act On Feedbackmentioning
confidence: 99%
“…In addition to self-reflection, student engagement in active learning may also be facilitated through peer assessment which provides students with the opportunity to evaluate, and be evaluated by, peers of a similar academic level and expertise who share a common knowledge and skill base (Boud andSoler 2016, Finn andGarner 2011). A range of studies in health professional education have explored the notion of peer assessment (Hodgson, Chan, and Liu 2014, Perera, Mohamadou, and Kaur 2010, Rush et al 2012, Speyer et al 2011. Rush and colleagues (2012), in their study of first-year nursing students, highlighted the positive effects of peer assessment and feedback.…”
Section: Introductionmentioning
confidence: 99%
“…This included students learning how to give and receive constructive criticism and students gaining insights into how others approach similar clinical problems. Receiving and providing quality feedback has been reported to enhance self-directed learning and improve professional performance (Hodgson, Chan, and Liu 2014, Perera, Mohamadou, and Kaur 2010, Rush et al 2012, Speyer et al 2011.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, double-marking, or having more than one teacher assign marks to an assignment is useful [13]. Similarly including peer assessments of student work is valuable [14] [15]. Including opportunities for self-assessment in grading practices is especially important [8] [16].…”
Section: Subjectivitymentioning
confidence: 99%